Framing Climate Goals in Terms of Cumulative CO2‐Forcing‐Equivalent Emissions - S. Jenkins; R. J. Millar; N. Leach; M. R. Allen (Geophysical Research Letters)
Abstract The relationship between cumulative CO2 emissions and CO2‐induced warming is determined by the Transient Climate Response to Emissions (TCRE), but total anthropogenic warming also depends on non‐CO2 forcing, complicating the interpretation of emissions budgets based on CO2 alone. An alternative is to frame emissions budgets in terms of CO2‐forcing‐equivalent (CO2‐fe) emissions—the CO2 emissions that would yield a given total anthropogenic radiative forcing pathway. Unlike conventional “CO2‐equivalent” emissions, these are directly related to warming by the TCRE and need to fall to zero to stabilize warming: hence, CO2‐fe emissions generalize the concept of a cumulative carbon budget to multigas scenarios. Cumulative CO2‐fe emissions from 1870 to 2015 inclusive are found to be 2,900 ± 600 GtCO2‐fe, increasing at a rate of 67 ± 9.5 GtCO2‐fe/yr. A TCRE range of 0.8–2.5°C per 1,000 GtC implies a total budget for 0.6°C of additional warming above the present decade of 880–2,750 GtCO2‐fe, with 1,290 GtCO2‐fe implied by the Coupled Model Intercomparison Project Phase 5 median response, corresponding to 19 years' CO2‐fe emissions at the current rate.